Medical tourism's impacts on health worker migration in the Caribbean: five examples and their implications for global justice - Jeremy Snyder; Valorie A. Crooks; Rory Johnston; Krystyna Adams; Rebecca Whitmore (Taylor & Francis Group, 2015)
Medical tourism is a practice where individuals cross international borders in order to access medical care. This practice can impact the global distribution of health workers by potentially reducing the emigration of health workers from destination countries for medical tourists and affecting the internal distribution of these workers. Little has been said, however, about the impacts of medical tourism on the immigration of health workers to medical tourism destinations. We discuss five patterns of medical tourism-driven health worker migration to medical tourism destinations: 1) long-term international migration; 2) long-term diasporic migration; 3) long-term migration and 'black sheep'; 4) short-term migration via time share; and 5) short-term migration via patient-provider dyad. These patterns of health worker migration have repercussions for global justice that include potential negative impacts on the following: 1) health worker training; 2) health worker distributions; 3) local provision of care; and 4) local economies. In order to address these potential negative impacts, policy makers in destination countries should work to ensure that changes in health worker training and licensure aimed at promoting the medical tourism sector are also supportive of the health needs of the domestic population. Policy makers in both source and destination countries should be aware of the effects of medical tourism on health worker flows both into and out of medical tourism destinations and work to ensure that the potential harms of these worker flows to both groups are mitigated.